Implementasi Kemampuan Membaca Huruf Hijaiyah melalui Flash Card Bahasa Arab pada Kelompok A di RA al Hikmah Ngampungan Bareng Jombang - Miftahillah Miftahillah; Ana Izzatul Khoiroh (SCHOLASTICA: Jurnal Pendidikan dan Kebudayaan, 1970)
Arabic flash card media is a card learning media that is used by teachers to learn learning in children in reading hijaiyah letters correctly and correctly, related to the development of RA age children (4-6 years) included in pre-operational walls while children cannot Think abstractly about an event or event, so the child understands it better. With the aim of this study to determine the implications of the use of Arabic flash card media in the ability to read group A hijaiyah letters at RA Al Hikmah Ngampungan Bareng Jombang. this research is a qualitative method with data analysis techniques using data collection on the results of children's assessment through a grid of research instruments which are then summarized in the results of the study. The population in this study were group A RA Al Hikmah students who collected 27 children with a sample of 6 children. the results can be seen by the increase in the score of the ability to read the hijaiyah letters in group A children so that the results of the study entitled "the ability to read hijaiyah letters through Arabic flash cards in group A in RA Al Hikmah Ngampungan Bareng Jombang" have been implicated in the results of children's activities.